Drug abuse: A Hindrance to Optimal Functioning of the Rural Learner’s Cognitive Capabilities - Nowell Chidakwa; Alfred Motalenyane Modise; Fumane Portia Khanare (Research in Social Sciences and Technology, 2023)
The article investigates four vulnerable learners and their histories of drug misuse in rural schools. The purpose of this study was to conduct a situational analysis with a view to understanding the current drug abuse situation in Zimbabwean rural schools and giving some recommendations on what needs to be done to lessen its effects. The study's mode of investigation was qualitative. As means of gathering data, focus groups and participatory research were used. The participatory research design employed by the study unearthed evidence that indicates that drug abuse has an adverse effect on a learner’s cognitive optimal functioning both in the community and school contexts. The study's findings point to the necessity of teaching parents how to prioritise their responsibilities and liberate them from the mental poverty they currently experience, which is a societal construct that keeps them from finishing their work with their learners. The study further found out that the absence of guidance and counselling exposes learners to more drug abuse cases and culture, thus having a two-pronged impact on the optimal functioning of rural learners. The study makes some recommendations for how the school and the community should work together and coordinate their efforts to manage the experiences of vulnerable students in order to achieve cognitive optimal functioning for rural learners in Zimbabwe.